ASSOCIATION NOTES. (The Accounting Review, 1961)
At the Queen's University, Canada, L. G. Macpherson, president of the Association of Canadian Schools of Commerce and Business Administration, reports that a number of topics of particular interest to teachers of accounting were included on the program of the fifth annual conference of the association held June 12 and 13, 1961 at Sir William George University, Montreal. At the Los Angeles State College, Los Angeles, California, Warren C. Bray has been appointed head of the Accounting Department. Robert H. Cojeen has been promoted to Professor at the Northern Illinois University, Illinois. William A. Paton, Jr. is leaving the faculty to accept a position at Florida State University. The first Montana Institute on Accounting at the Montana State University, Montana, sponsored by the School of Business Administration was held between June 14 and 16, 1961. Eric L. Kohler was the banquet speaker. Donald J. Emblem and Dorsey E. Wiseman spoke on profit planning for small business. Jack Kempner presented a paper, "Development of Accounting and Auditing Standards."